Comparison of greenhouse and field resistance of bean varieties to Empoasca kraemeri (Homoptera Cicadellidae) - Eskafi, F.M.; Schoonhoven, Aart van (1978)
Resistance of 360 var. of Phaseolus vulgaris to Empoasca kraemeri was evaluated in the greenhouse. Subsequent field evaluations were made of 30 promising var. when 30 days old. Seedlings in the greenhouse were infested with field-collected adults for 3 days, and resistance to 1st generation nymphs was tested. There was a highly significant positive correlation between the no. of nymphs present on the plant and feeding damage (expressed as quality) under low, but not high infestation pressure under greenhouse but not field conditions. There was no correlation between no, of nymphs found on the 30 var. in either the greenhouse or the field, but there was a highly significant correlation for feeding damage (quality). No correlation was found in the field between the no. of nymphs and plant height or vol (width(2) x height). The relationship between plant quality (resistance) in the greenhouse and field evaluations was highly significant as measured by a rank correlation test. (AS)